Mrs. Lane is a pain! - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2014)
"It's time for the annual Ella Mentry School talent show, and this year Principal Klutz has hired a wacky professional, Mrs. Lane, to help the kids with their talents"--
Keywords: Schools -- Juvenile fiction; Talent shows -- Juvenile fiction; Humorous stories